An exploratory study of balanced scorecard practices: preliminary evidence from Thailand / Wasatorn Shutibhinyo - Shutibhinyo, Wasatorn (Accounting Research Institute (ARI), 2012)
This paper develops a framework for Balanced Scorecard (BSC) stage classification by considering the BSC attributes embedded in firm's performance measurement system. Employing this framework to explore the BSC application among Thai listed companies reveals that based on survey data, 69% are classified as BSC users. Compared to the selfassessed responses about BSC application, 38% misclassify themselves. This supports the different interpretations of BSC expressed in prior studies and highlights the importance of proper classification of BSC application before performing any determinant or consequence tests. The developed BSC framework can be applied to future research as researchers should consider BSC attributes, not firms' self assessed responses about BSC application, in order to mitigate the dissimilar interpretations of BSC concept. Additionally, exploring the BSC practices among Thai listed firms in all industries complements previous studies on BSC application mostly performed in specific industries in US and Europe